1991
DOI: 10.2514/3.46033
|View full text |Cite
|
Sign up to set email alerts
|

Calculating time-correlated gust loads using matched filter and random process theories

Abstract: This paper describes and illustrates two ways of performing time-correlated gust-load calculations. The first is based on matched filter theory, the second on random process theory. Both approaches yield theoretically identical results, represent novel applications of the theories, are computationally fast, and may be applied to other dynamic-response problems. A theoretical development and example calculations using both matched filter theory and random process theory approaches are presented. Nomenclature G(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 4 publications
(2 reference statements)
0
14
0
Order By: Relevance
“…(2)] and the maximum responsefunctional[Eq. (4)], we can now formally state the problem addressed in this paper to be "Find the global maximum of f when x.t / is restricted to the set of inputs that satisfy the energy constraint U .x/ D U .…”
Section: Problem De Nitionmentioning
confidence: 99%
See 2 more Smart Citations
“…(2)] and the maximum responsefunctional[Eq. (4)], we can now formally state the problem addressed in this paper to be "Find the global maximum of f when x.t / is restricted to the set of inputs that satisfy the energy constraint U .x/ D U .…”
Section: Problem De Nitionmentioning
confidence: 99%
“…3¡9 In stress analysis, 1;2 a study is made of the various responseloads, referred to as time-correlated, or balanced, loads of a system when one particular load, known as the reference load, is maximal. When the system is linear, the values of each output can be calculated either by a cross-correlationtechnique 2 or by a technique based upon matched lter theory (MFT) 2 ; the results of both methods being theoretically identical. 2 When the system is nonlinear, such techniques are no longer applicable.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Ref. 3, this sample is referred to as the matched excitation waveform, since it is derived from, or matched to, the impulse response of the combined turbulence/aircraft-load lter through Eq. (3).…”
Section: Mathematical Development Linear System Responsementioning
confidence: 99%
“…NASA conducted the evaluation of the SDG method, focusing on its overlap with the existing linear methods. 2 In the course of these studies, it was found that the concept of the matched lter from signal processing theory 3,4 could be applied to the analysis of time-correlated, worst-case gust loads for mathematically linear aircraft models. Much of the work on the matched lter approach to gust loads analysis that followed had been geared toward a fundamental understanding of the implications of the matched lter theory interpretation of the gust loads analysis problem, as well as various attempts at extending the techniques to nonlinear aircraft models.…”
mentioning
confidence: 99%